VITAMINS AS IMMUNOMODULATORS AND ANTITUBERCULOSIS TARGETS - Andreea-Daniela Meca; Ana Marina Andrei; Elena Camelia Stănciulescu; Cătălina-Gabriela Pisoschi (Romanian Dental Association for Education, 2020)
Tuberculosis is a major global burden nowadays, caused by species of Mycobacterium which have the ability to survive in difficult and stressful conditions inside the lungs, necrotic lesions, epithelial tissue, spine, cervical nodes and brain. This disease represents a fight between oxidative species of oxygen, markers of the oxidative stress, and peptides, cytokines and neutrophils, biomarkers of the innate and adaptive immunity. The human susceptibility to be infected can be related to blood concentrations of vitamin D, which interferes with the macrophage development, monocyte activation and signalization through vitamin D receptor. Vitamin D also stimulates cathelicidin (LL-37), an antimicrobial peptide, involved in autophagy and apoptosis, induced inside bacterial cells, therefore it is underlined its immunomodulatory and anti-inflammatory roles in infectious diseases. Moreover, vitamin C has shown antimycobacterial effect, both antioxidant and prooxidant properties maintaining redox stress mechanisms. On the other hand, biotin and thiamine seem to be required for establishment of the Mycobaterium tuberculosis infection, merging the need to elaborate new antituberculotic agents able to act as inhibitors of their biosynthesis.